O processo civil participativo como instrumento para o fortalecimento do estado democrático de direito - Gomes, Gustavo Gonçalves (2012)
This dissertation studies the participative civil procedure and has as its aim the analysis of Brazilian current procedural framework - dated of 1973 - according to the bedrock premises of the Legal Democratic State and in compliance with the Brazilian Federal Constitution of 1988. In order to achieve this major objective, the research in the methodological level is supported by the deductive method and the case law research technique. Concerning the structure, this paper is divided in three chapters: the first one explains the Legal Democratic State and the Procedure . The second one analyses the participative behaviour of the judges in lawsuits governed by the Brazilian Procedure Law system. Finally, the last chapter compares factors that contribute to the construction of a participative procedure model. The conclusion reached is that the modern civil procedure law cannot survive anymore without its due compliance with substantive law. In this sense, it is necessary to revisit the instrumental premises of procedure law, in a way that it may contribute more and more to the rendering of quick, fair and adequate judicial pronouncements. In order to develop a new procedural framework in compliance with actual necessities of the Brazilian society, a proactive behaviour of all becomes mandatory. The most reasonable pathway to achieve this objective is to develop of a participative civil procedure system as a mechanism to enhance democratic state of law's strength. Through this constitutionally sustainable procedure law model, the judges would have a structural role in conducting the lawsuits towards a singular direction, with the purpose of enhancing judicial decisions rendering. A participative performance of the judges in lawsuits is one of the main aims of the society, as the latter clearly acknowledges that judges hold the power/duty of optimizing judicial decisions rendering, in a way that it may bring a better quality and more effectivity to the whole system. Notwithstanding, there are other problems to be faced, such as the lack of structure in the Judiciary and its current crisis (which is different from the procedure law crisis). However, as evidenced in any other company or organization, the Judiciary needs to be surrounded by active, proactive and creative professionals. Also, a profound change of values in the juridical environment is necessary for a satisfactory evolution